Trend analysis and prediction of temperature change in the continental, Thailand - Phumkokrux Nutthakarn (Glasnik Srpskog Geografskog Društva, 2023)
Diurnal Temperature Range (DTR) is one of global warming indicator which using only daily minimum temperature (TMin) and daily maximum temperature (TMax) for calculation. The study aims 1) to analyse trend of TMax, TMin and DTR over the early period of 21st century (1987 - 2020) and 2) to forecast and analyse trend of TMax, TMin and DTR over the mid and late period of 21st century (2021 - 2040 and 2041-2100) using MIROC5 (rcp85) model, cooperated with EQM Statistical downscaling method. TMax, TMin, and and DTR trends of all periods were investigated by Mann Kendall Trend Test and Sen’s slope, then presented in the form of spatial maps. The most of TMax and TMin trends for all season and all regions tended to be increasing from year by year with the large increasing of changing in Northern and Northeast region especially in Winter, except for the last period which had a large increasing in Summer. However, DTR trends were quietly fluctuated with the large decreasing of changing in Eastern and Southern part, but the trends become to increase in the last period. A large DTR decreasing of changing usually occurred in Winter and Rainy season. The TMax and TMin of all periods were expanding year by year and leading the DTR decreased in the first and second period, however, a changing of TMax and TMin rate leaded DTR increasing for the last period. It is a good signal for heat transfer performance which can help the earth cooling in night time.